2007
DOI: 10.1126/science.1131754
|View full text |Cite
|
Sign up to set email alerts
|

Mass-Independent Sulfur Isotopic Compositions in Stratospheric Volcanic Eruptions

Abstract: The observed mass-independent sulfur isotopic composition (Delta33S) of volcanic sulfate from the Agung (March 1963) and Pinatubo (June 1991) eruptions recorded in the Antarctic snow provides a mechanism for documenting stratospheric events. The sign of Delta33S changes over time from an initial positive component to a negative value. Delta33S is created during photochemical oxidation of sulfur dioxide to sulfuric acid on a monthly time scale, which indicates a fast process. The reproducibility of the results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
215
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 156 publications
(231 citation statements)
references
References 22 publications
14
215
2
Order By: Relevance
“…Agung and Mt. Pinatubo eruptions, sulfate is initially positive in both δ 34 S and Δ 33 S. The subsequent change in sign of Δ 33 S is associated with a significant decrease of δ 34 S, with a slope (Δ 33 S/δ 34 S) of ∼0.1 (8). Moreover, there is broad agreement in Δ 36 S/Δ 33 S after both Mt.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Agung and Mt. Pinatubo eruptions, sulfate is initially positive in both δ 34 S and Δ 33 S. The subsequent change in sign of Δ 33 S is associated with a significant decrease of δ 34 S, with a slope (Δ 33 S/δ 34 S) of ∼0.1 (8). Moreover, there is broad agreement in Δ 36 S/Δ 33 S after both Mt.…”
mentioning
confidence: 66%
“…A series of groundbreaking studies has shown that sulfur isotopes in sulfate from Plinian eruptions show mass-independent fractionation (MIF) (6)(7)(8). Carbonyl sulfide (OCS) is thought to be the main source of background SSA in volcanically quiescent periods (9), and the reactions breaking down OCS, mainly photolysis, show no evidence of sulfur MIF (10)(11)(12)(13).…”
mentioning
confidence: 99%
“…Laboratory experiments have demonstrated that the S-MIF originates during SO 2 photolysis at short wavelengths (λ < 300 nm), producing sulfate with positive Δ 33 S and negative Δ 36 S values, and a wide array of slopes (Δ 36 S/Δ 33 S), ranging from −1.1 to − 4.3 depending on wavelength (12), pressure, and composition of the gaseous mixture (13) . The observations suggest that the S-isotope anomaly in sulfate aerosol in 1998-1999 is a consequence of SO x (SO 2 , SO 3 ) photochemistry (5,6,12,14) in the short UV (<200 nm) region of the solar spectrum above the ozone layer (>25 km) where this wavelength is available in the present-day atmosphere, as will be discussed. The S-isotopic anomalies observed in volcanic sulfate aerosols are accompanied by a significant increase in sulfate concentration (4,5,11).…”
Section: Significancementioning
confidence: 93%
“…The observations suggest that the S-isotope anomaly in sulfate aerosol in 1998-1999 is a consequence of SO x (SO 2 , SO 3 ) photochemistry (5,6,12,14) in the short UV (<200 nm) region of the solar spectrum above the ozone layer (>25 km) where this wavelength is available in the present-day atmosphere, as will be discussed. The S-isotopic anomalies observed in volcanic sulfate aerosols are accompanied by a significant increase in sulfate concentration (4,5,11). The Pinatubo and Cerro Hudson eruptions in 1991 produced a factor of 3.7 sulfate concentration increase in the snow record.…”
Section: Significancementioning
confidence: 93%
See 1 more Smart Citation